Curcuma mangga-Mediated Synthesis of Gold Nanoparticles: Characterization, Stability, Cytotoxicity, and Blood Compatibility - Foo, Y.Y.; Periasamy, V.; Kiew, L.V.; Kumar, G.G.; Malek, S.N.A. (MDPI, 2017)
The utilization of toxic chemicals as reducing and stabilizing agents in the preparation of gold nanoparticles (AuNPs) has increased in vivo toxicity and thus limited its application in clinical settings. Herein, we propose an alternative method of preparing highly stable AuNPs, where non-toxic Curcuma mangga (CM) extract was used as a single reducing and stabilizing agent to overcome the aforementioned constraints. The morphological images enunciated that the homogeneously dispersed AuNPs exhibited spherical morphology with an average particle diameter of 15.6 nm. Fourier Transform infrared (FTIR) and cyclic voltammetry analysis demonstrated that carbonyl groups of terpenoids in CM extract played an important role in the formation and stabilization of AuNPs. Green-synthesized AuNPs were found to have good stability in physiological media after 24 h of dispersion. The AuNPs were also cytocompatible with human colon fibroblast cell (CCD-18Co) and human lung fibroblast cell (MRC-5). Hemocompatibility tests revealed that the AuNPs were blood-compatible, with less than 10% of hemolysis without any aggregation of erythrocytes. The current study suggests potential in employing a CM-extract-based method in the preparation of AuNPs for anticancer diagnosis and therapy.